Amikacin monotherapy for sepsis caused by panresistant Pseudomonas aeruginosa - Layeux, Brice; Taccone, Fabio Silvio; Fagnoul, David; Vincent, Jean-Louis; Jacobs, Frédérique (Antimicrobial agents and chemotherapy, 2010)
Two patients with severe sepsis due to panresistant Pseudomonas aeruginosa, deteriorating despite therapy with colistin and β-lactams, were cured with a high daily dose (25 to 50 mg/kg) of amikacin to obtain a peak/MIC ratio of at least 8 to 10 (MIC = 16 μg/ml). Concomitant use of continuous venovenous hemodiafiltration (CVVHDF) provided no deterioration in renal function after treatment. High dosage of aminoglycosides combined with CVVHDF may represent a valuable therapeutic option for infection due to multiresistant pathogens.